2010
DOI: 10.1002/cjoc.201090315
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry and Electrocatalysis Behaviors of Glucose Oxidase Based on Hyaluronic Acid‐Carbon Nanotubes‐Ionic Liquid Composite Film

Abstract: Multi-walled carbon nanotubes (MWNTs) were dispersed in the ionic liquid [BMIM] [BF 4 ]-MWNTs could obviously improve the diffusion of ferricyanide toward the electrode surface. The experimental results of CV showed that a pair of well-defined and quasi-reversible peaks of GOx at the modified electrode was exhibited, and the redox reaction of GOx at the modified electrode was surface-confined and quasi-reversible electrochemical process. The average surface coverage of GOx and the apparent Michaelis-Menten c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…BMIMBF4 has high viscosity (99.9 cP at 20 °C [39]; which may increase the resistance), but may support charge transport by behaving as a fortifying source of ion carriers (conductivity of 0.35 S/m at 25 °C [39,40]. This electrochemical behavior is in agreement with those observed by Zhang et al [41] and Shangguan et al [42]. (Fig.…”
Section: Electrochemical Characterizationsupporting
confidence: 89%
See 3 more Smart Citations
“…BMIMBF4 has high viscosity (99.9 cP at 20 °C [39]; which may increase the resistance), but may support charge transport by behaving as a fortifying source of ion carriers (conductivity of 0.35 S/m at 25 °C [39,40]. This electrochemical behavior is in agreement with those observed by Zhang et al [41] and Shangguan et al [42]. (Fig.…”
Section: Electrochemical Characterizationsupporting
confidence: 89%
“…(2):(2)ks=mnFν∕RTwhere m is the parameter related to peak potential separation (V), n the number of electrons involved in the reaction, ν is the scan rate (V/s) and all other symbols have their usual meanings. A ks value of 0.35 s −1 was obtained being in the same range as those described for some enzymatic biosensors (0.51 s −1 for glucose oxidase [42]; 0.55 [57] and 0.655 s −1 [58] for horseradish peroxidase; 0.7 s −1 for chloroperoxidase [59]; and 0.78 s -1 for choline oxidase based-biosensor [53]) and heme-based biosensors (0.406 s −1 [60], 0.5525 s −1 [61], 0.63-0.70 s −1 [55] and 0.725 s −1 [62] for hemoglobin based-biosensors; 0.610 s −1 [63] and 0.675 s −1 [31] for myoglobin based devices) with BMIMBF4 (Table 1S-2S, Supplementary Material). This information demonstrated that the electron transfer between NOR and the modified electrode is efficiently mediated by the developed nanocomposite.…”
Section: Direct Electron Transfer Behavior Of Nor On the Pge/[mwcnts/supporting
confidence: 59%
See 2 more Smart Citations
“…Other approaches such as the addition of metal ions or the addition of mineralizing species have also been shown to be efficient at forming HA-based hydrogels. , On the other hand, it was recently reported that the addition of carbon nanotubes (CNTs) could also lead to the formation of HA gels. These gels are achieved at relatively low concentrations without any covalent modifications of the polymer. HA–CNT composites have also been investigated as biofibers or as electrode materials for bioelectrochemical applications. The new HA–CNT biogels have already demonstrated promising properties and biofunctionalities. They are biocompatible, electrically conductive, and can serve as scaffolds with electrically stimulated delivery of bioactive molecules such as neurotrophins .…”
Section: Introductionmentioning
confidence: 99%